Urban pioneer : interiors inspired by industrial design - Emslie, Sara (Ryland Peters & Small, 2017)
A decline in manufacturing in city centres meant that many warehouses and factories became vacant, attracting the first wave of urban pioneers--artists and creatives seeking cheap rents and large interiors to use as studio spaces. Since then, industrial areas in many cities have become sought-after residential districts and urban regeneration has gone from strength to strength. Nowadays the trend shows no sign of waning, with a second generation of urban pioneers cleverly converting former lofts, warehouses, schools, factories, offices and retail spaces into highly desirable homes full of personality and soul. In Urban Pioneer, Sara Emslie investigates the practice for transforming non-residential spaces into homes, the key elements of the look--from exposed brickwork to copper piping and metal roof trusses--and the related rise in the popularity of industrial design. She then explores twelve inspiring and varied real-life homes that showcase the very best of the Urban Pioneer look